Improved the interfacial characteristics of carbon fiber/polyamide 6 composites by synthesizing polydopamine rapidly on the carbon fiber surface with ultrasound-assisted. (22nd March 2023) - Sun, Na; Zhu, Bo; Gao, Xueping; Qiao, Kun; Zhang, Ye; Wang, Baoming; Fan, Jiayan; Yu, Kuan; Liu, Chaohong; Li, Chengsen; Zheng, Qi
Abstract: Poor interfacial compatibility is the main factor restricting the improvement of mechanical properties of carbon fiber (CF) reinforced polyamide 6 (PA6) composites. In this paper, we exploited the feature that polydopamine (PDA) can be rapidly synthesized under hypoxic conditions by ultrasound, and the PDA coating was generated quickly and uniformly on CF to modify the interface of the composites. The results show that CF could be entirely coated by impregnating CF in PDA-Tris solution for 1 h under the ultrasound. The introduction of PDA coating significantly enhanced the wettability of the CF surface. The application of ultrasound greatly improved the coating efficiency of PDA on CF, especially on the inner layer of the CF bundle. Compared with desized CF/PA6 composites, the interlaminar shear properties of PDA-modified CF/PA6 composites are improved by 21.07%. The PDA coating binds well to both CF and PA6, so when the composites were exposed to shear force, the interlayer cracks spread along the PDA and PA6 layers instead of the CF surface, resulting in greater resistance to crack propagation. It is the primary reason for improving the composites' interface performance. Therefore, ultrasound-assisted rapid synthesis PDA on CF can effectively improve the interface characteristics of CF/PA6 composites. Graphical abstract: Image 1 Highlights: Coating polydopamine (PDA) on carbon fiber (CF) improved the CF's wettability and tensile strength. Ultrasound-assisted significantly accelerated the production rate of PDA on CF. The ultrasound's cavitation effect greatly reduced the difference between the inner and outer coatings of fiber bundle. The aggregation state of PDA can evolve farther toward self-assembly with the ultrasound. After modification, the interlaminar shear strength of CF/PA6 composites was increased by 21.07%.